"Are you sure?": Relations between sexual identity, certainty, disclosure, and psychological well-being. Issue 2 (3rd April 2018) - Bejakovich, Tamara; Flett, Ross
ABSTRACT: Lesbian, gay, bisexual, and questioning (LGBQ) individuals have repeatedly demonstrated lower levels of psychological well-being than their heterosexual counterparts. The literature suggests that bisexually identified participants are more vulnerable to poor outcomes, yet some studies have called this statement into question. This study aimed to address this inconsistency, and investigate how factors related to cognitive dissonance, such as identity disclosure and certainty, influence well-being in the LGBQ subgroups. We used web-based sampling, and distributed an online questionnaire assessing identity disclosure, certainty, and three variables of psychological well-being (affect, happiness, and life satisfaction). This survey was predominantly advertised in and completed by people in New Zealand. Participants who were over 18 and had the technological skills and English proficiency to complete the survey were eligible for this study, resulting in a final sample of 402. Consistent with past research, participants with LGBQ identities had lower rates of psychological well-being than those identifying as heterosexual. Additionally, as expected, identity certainty and disclosure of identity were associated with higher psychological well-being. Cognitive dissonance theory may be a useful contributor to the Minority Stress Theory framework, as it expands our understanding of how internal stressors affect the complex relationship between sexual identity and well-being. Further investigation into sexual identity (particularly the development of certainty, and the "coming out" decision) and psychological well-being is recommended for future research.